Biocomplex Mitrofix as a new alternative to reconstructive surgery of mitral valve – preliminary observations and results - Skiba, Jacek; Kołtuniewicz, Rafał; Sukiennik-Kujawa, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Mitral valve repair procedures are preferable methods of treatment for patients with mitral valve dysfunction in modern cardiothoracic surgery. It is nowadays an alternative to mitral valve replacement. Between 23.05.11 and 13.10.11 we performed 8 Mitrofix device implantations. We report our preliminary results of the first 4 cases with full 3-month follow-up.